Covid-19 dan Filsafat Ilmu: Sebagai Gangguan Dalam Pembaharuan - Arya Luthfi Permadi (LPPM STISIP Persada Bunda, 2022)
This paper analyzes a new finding in the philosophy of science through a new disturbance; Covid-19. Covid-19 as a nuisance is measured using the Kilkki-based nuisance framework chart. This measurement will provide clarity as to whether Covid-19 can be categorized as a new disorder or just a disorder that has been found before such as the Spanish Flu. This study uses a descriptive-qualitative analysis model, the type of research is library research, as well as data collection methods, namely documentaries, books, journals, theses, reports and internet sites. The scope of this research is the Covid-19 pandemic by taking into account the two previous major pandemics; Spanish Flu and SARS. The results of this study indicate that covid-19 fulfills every aspect of the Kilkki disorder framework. This is what distinguishes Covid-19 from previous pandemics, including the two that have received the most attention; Spanish Flu and SARS. This is what answers why Covid-19 has not been able to be overcome with methods that have succeeded in stopping the rate of transmission and spread of the previous pandemic virus. In fact, although similar steps have been taken, because it is a new disorder, a renewal in the philosophy of science is needed to answer the final result of a new pandemic; covid-19.